'A Stone Within': Visual Poetry & Wellbeing in the work of Alec Finlay and Thomas A. Clark. Issue 1 (16th January 2017) - Tarbuck, Alice
Abstract : Thomas A. Clark is a poet and visual artist, born in Greenock in 1944. His work is characterized by its concentration on form, its attention to the materiality of language, and its focus on the natural world. His visually innovative poetry has been associated with a variety of movements and genres including the Concrete Poetry movement of the 1960s and, more recently, the resurgence in writing about the environment referred to as the New Nature Writing. In addition to publishing more traditional page poetry, Clark produces work in a wide variety of media – from folded paper forms to large-scale installations, sound works and prints. Additionally, Clark and his wife Laurie were among the first artists to open 'artist run spaces' in Britain, having run the Cairn Gallery since 1986. One poet regularly displayed in the Cairn Gallery is Alec Finlay (1966 –), whose work, like Clark's, uses innovative form as a means through which to encounter the natural world. In particular, Finlay works with variations on sets of objects over time: nest-boxes, cloth tape, and botanic labels all make an appearance in his work, alongside neon and new technology.